Laparoscopic vs. Open Abdominal Radical Hysterectomy for Cervical Cancer: A Single-Institution, Propensity Score Matching Study in China - Yuan, Zhen; Cao, Dongyan; Yang, Jie; Yu, Mei; Shen, Keng; Yang, Jiaxin; Zhang, Ying; Zhou, Huimei (Frontiers in Oncology, 2019)
Study Objective: To compare the surgical and oncologic outcomes between open abdomen radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH) for cervical cancer. methods: Retrospective observational study with propensity score matching was used to ensure balanced groups for ARH and LRH. One hundred ninety-eight women with cervical cancer, 99 treated using ARH and 99 LRH, between January 2012 and December 2014. Outcomes included disease-free survival (DFS), overall survival (OS), intra-operative factors, post-operator recovery, urinary retention, and adverse events Main Results: Compared with ARH, LRH was associated with lower volume of blood loos (P<0.001) and transfusion rate (P<0.001), with a broader resection of the parametrium (P<0.001). Post-operatively, the time to first flatus was shorter for LRH than ARH (P<0.001) but the rate of urinary retention was higher for LRH (22.2%) than ARH (8.1%; P=0.009). DFS and OS were similar between groups. Conclusion: Compared with ARH, LRH provided better intra-operative and post-operative outcomes, with no significant different in oncologic outcomes and survival. Urinary retention remains a clinical issue to improve with LRH. The technology of LRH has been improved in China to face the inconsistent results of oncologic outcomes in previous studies. Whether these improvements could be effective needs to be investigated in the future.